Gibbs Free Energy of Formation of Synthetic Cryptomelane - Raphael Hypólito; José Vicente Valarelli; Rudolf Giovanoli; Silvania M. Netto (CHIMIA)
Cryptomelane with a formal composition of K0.88Mn(III)0.24Mn(IV)7.60O16.00∙0.33H2O was precipitated from a solution of sulfuric acid containing dissolved manganese sulfate. The oxidation state of manganese in solution was controlled by bubbling pure oxygen gas through and the pH was raised from 1.00 to 2.90 by addition of KOH. Measurements of pH and Eh as well as determination of ion activities in equilibrium with the obtained solid led to a pH = f(Eh) curve with an inclination corresponding to the synthesis equation: